Modeling obesity-driven pancreatic carcinogenesis: a review of current In Vivo and In Vitro models of obesity and pancreatic carcinogenesis - Kfoury, Sally; Michl, Patrick; Roth, Laura (Cells, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is the most common pancreatic malignancy with a 5-year survival rate below 10%, thereby exhibiting the worst prognosis of all solid tumors. Increasing incidence together with a continued lack of targeted treatment options will cause PDAC to be the second leading cause of cancer-related deaths in the western world by 2030. Obesity belongs to the predominant risk factors for pancreatic cancer. To improve our understanding of the impact of obesity on pancreatic cancer development and progression, novel laboratory techniques have been developed. In this review, we summarize current in vitro and in vivo models of PDAC and obesity as well as an overview of a variety of models to investigate obesity-driven pancreatic carcinogenesis. We start by giving an overview on different methods to cultivate adipocytes in vitro as well as various in vivo mouse models of obesity. Moreover, established murine and human PDAC cell lines as well as organoids are summarized and the genetically engineered models of PCAC compared to xenograft models are introduced. Finally, we review published in vitro and in vivo models studying the impact of obesity on PDAC, enabling us to decipher the molecular basis of obesity-driven pancreatic carcinogenesis.